The logic behind secondary buyouts: Empirical evidence from Finland - Rantala, Antti (My University, 2016)
The purpose of this thesis is to study the logic behind the secondary buyouts in Finland between 2002 and 2014 using the hand-collected sample of buyouts. The thesis investigates whether the secondary buyouts are motivated by efficiency gains or driven by market conditions or liquidity demand. In addition, the role of collusion in secondary buyouts is examined. Finally, this thesis studies how secondary buyout are priced. Value creation is the basis of private equity industry. Previous academic literature shows private equity buyouts has positive impact on target companies’ operating performance. In the context of value creation the logic of secondary buyout is still a puzzle. This thesis investigates with year-by-year examination the development of the operating performance after secondary buyouts. In order to find out the alternative motives for secondary buyouts, probit model is used to find out how equity and debt market condition and liquidity demand effect on the exit route. To examine the role of collusion in secondary buyouts cross-participation matrix is built to identify possible trade patterns. The pricing of secondary buyouts is studied with comparable industry transaction method against first-time buyouts using the Ordinary Least Squares regression. Evidence of the study do not show efficiency gains for target companies in secondary buyouts. Results suggests that market condition is the main driver of secondary buyouts. When debt market is favorable, the probability of exiting through secondary buyout increases significantly. On the other hand, favorable equity market is found to increase the probability of other exit routes, IPO and the selling strategic buyer, although with less significant results. In addition, results also shows that secondary buyouts are associated with higher value compared to first-time buyouts. The higher value is significantly driven by favorable debt market condition and the size of the target company.
Keywords: Secondary buyout; Private equity; SBO; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|